Beyond toddlerdom keeping five-to-twelve-year-ols on the rails - Green, Christopher (Vermilion, 2000)
Intended for those parents who are in need of calm and wise advice on parenting the 5-12 year age group. This book enables parents to understand their child's needs and development during their pre-teen years. It takes account of the physical, psychological and sociological influences that are of importance during this time.